2011
DOI: 10.1007/s10815-011-9549-1
|View full text |Cite
|
Sign up to set email alerts
|

Embryo quality, blastocyst and ongoing pregnancy rates in oocyte donation patients whose embryos were monitored by time-lapse imaging

Abstract: Thus we concluded that time-lapse monitoring in the EmbryoScope does not impair embryo quality while allowing for morphological, spatial and temporal analysis of embryo development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
124
2
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(133 citation statements)
references
References 13 publications
5
124
2
2
Order By: Relevance
“…We therefore believe the embryos in the two groups to be comparable and our results to be valid and applicable in other settings. The higher rate of blastocyst development reported in the study by Cruz et al [5] (54.8 % in the timelapse incubator and 50.6 % in the standard incubator) compared to our study (24.9 % in the time-lapse incubator and 23.2 % in the standard incubator) supports the assumption that the oocytes in the two studies were not of comparable quality. An additional contributing factor to the observed discrepancy in blastocyst rates was, that oocytes were allocated to the two types of incubators after confirmed fertilization in the study by Cruz et al [5], in contrast to our study, where randomization was done before confirmed fertilization.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…We therefore believe the embryos in the two groups to be comparable and our results to be valid and applicable in other settings. The higher rate of blastocyst development reported in the study by Cruz et al [5] (54.8 % in the timelapse incubator and 50.6 % in the standard incubator) compared to our study (24.9 % in the time-lapse incubator and 23.2 % in the standard incubator) supports the assumption that the oocytes in the two studies were not of comparable quality. An additional contributing factor to the observed discrepancy in blastocyst rates was, that oocytes were allocated to the two types of incubators after confirmed fertilization in the study by Cruz et al [5], in contrast to our study, where randomization was done before confirmed fertilization.…”
Section: Discussionsupporting
confidence: 74%
“…The higher rate of blastocyst development reported in the study by Cruz et al [5] (54.8 % in the timelapse incubator and 50.6 % in the standard incubator) compared to our study (24.9 % in the time-lapse incubator and 23.2 % in the standard incubator) supports the assumption that the oocytes in the two studies were not of comparable quality. An additional contributing factor to the observed discrepancy in blastocyst rates was, that oocytes were allocated to the two types of incubators after confirmed fertilization in the study by Cruz et al [5], in contrast to our study, where randomization was done before confirmed fertilization. Cruz et al [5] consequently calculated blastocyst rates on the basis of a smaller population with higher chance of blastocyst development, which obviously results in higher blastocyst rates.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Evaluation of embryos in vitro has undergone a dramatic change in the past few years with the introduction of time-lapse imaging. This novel technique enables acquisition of dynamic images of embryo development [6,10,[28][29][30]. It has been proposed that the information acquired regarding the kinetics of embryo cleavage, either with or without use of standard static embryo morphology grading, will greatly improve successful selection of the most viable embryo for transfer.…”
Section: Discussionmentioning
confidence: 99%